INVESTIGATING THE IMPACT OF OPERATIONAL BUDGETING ON THE PERFORMANCE OF TEXTILE WORKSHOPS )CASE STUDY: WASIT-IRAQ TEXTILE AND WEAVING FACTORY) (World Bulletin of Management and Law, 2022)
Budgeting is one of the financial systems that without reforming the long - term reform of each organization's ratio at any level has specific and pre - defined goals that achieve the goals require proper planning and implementation. It requires optimal and proper distribution of resources and their control. Managers in the field of production are thinking of budgeting in different circles of relevant units so that they can maximize its performance by planned budgeting to each unit and to meet the needs of customers to have a positive impact on the financial performance of the complex. The purpose of this study is to investigate the impact of operating budgeting on the performance of textile workshops (Case Study: Textile and Iraqi -weaving plant). In this regard, the statistical population of the study includes the staff of a textile company in Iraq. The sample size is 12, with 80 distribution questionnaires and 77 questionnaires received. In this study, the standard questionnaire was used to collect information. Information analysis was done using SPSS and PLS. The results of the analysis of hypotheses showed that there is a significant relationship between operational budgeting on the performance of textile workshops in Iraq's intermediary province and there is a significant relationship between budget planning on the performance of the textile workshop in Iraq. There is a significant relationship between the budget partnership over the performance of the textile workshop in the Iraqi province, and there is a significant relationship between the budget control over the performance of the textile workshop in the Iraqi province
Keywords: pressures; world; province; performance